1993
DOI: 10.1530/jrf.0.0990335
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the marsupial sperm acrosome reaction in vitro by treatment with diacylglycerols

Abstract: The diacylglycerol DiC8 (1,2-dioctanoyl-sn-glycerol; 100 mumol l-1) was found to induce acrosomal loss in 70% of wallaby spermatozoa and 40% of possum spermatozoa after incubation for 120 min. If 10 mumol calcium ionophore l-1 was present, the time required to reach these end points was reduced to 30 and 60 min, respectively. The diacylglycerol OAG (1-oleoyl-2-acetyl-sn-glycerol; 100 mumol l-1) produced some acrosomal loss, particularly when 10 mumol calcium ionophore l-1 was present, but when the ionophore wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Addition of DAG or membrane-permeant phorbol esters triggers acrosomal exocytosis in spermatozoa of different species [18][19][20][21]. It has also been demonstrated that DAG formation during acrosomal exocytosis is differentially regulated by transducing pathways activated by physiological agonists [22].…”
Section: Introductionmentioning
confidence: 99%
“…Addition of DAG or membrane-permeant phorbol esters triggers acrosomal exocytosis in spermatozoa of different species [18][19][20][21]. It has also been demonstrated that DAG formation during acrosomal exocytosis is differentially regulated by transducing pathways activated by physiological agonists [22].…”
Section: Introductionmentioning
confidence: 99%
“…Possum and wallaby semen was collected by electroejaculation (Rodger and White, 1978;Rodger and Pollitt, 1981;Sistina et al, 1993). Possum and wallaby spermatozoa were 'swum-up' into phosphate-buffered saline (PBS) as described previously (Mate and Rodger, 1991 [possum]; Sistina et al, 1993 [wallaby]).…”
Section: Methodsmentioning
confidence: 99%
“…Acrosomal proteins were released from possum spermatozoa, collected from the tail of the epididymis, by treatment with 1,2-dioctanoyl-sn glycerol (DiC 8 , Sigma) as described previously (Sistina et al, 1993). Briefly, possum spermatozoa (10 7 /ml) were treated with 100 µM DiC 8 for 30 min at 37°C.…”
Section: Immunisations and Cell Fusionmentioning
confidence: 99%
“…Aliquots (50 l) of unattached sperm were drawn after vigorous pipetting 5 times from the same well at 0, 2, 4, and 6 h of incubation each time and were assessed for sperm concentration, motility, viability, acrosome status, and sperm head-to-tail orientation by standard procedures [25]. Briefly, the acrosome status of the unattached spermatozoa was evaluated after fixation in paraformaldehyde and staining with Bryan's stain, an equal combination of 0.1% (w:v) each of fast green FCF, eosin Y, and flavianic acid (all Sigma Chemical Company) in 1% acetic acid.…”
Section: Sperm Assessmentsmentioning
confidence: 99%